Wyznaczanie Naprężeń Wzdłuż Osi Symetrii w Zagadnieniu Izometrycznym na Podstawie Elastooptycznego Obrazu Izochrom - Wojnar, R. (Engineering Transactions, 1972)
Analysis of the state of stress on the sole basis of fringe pattern image is a very time-consuming 'procedure, even in the case when the axis of symmetry is only concerned along which the directions of principal stresses are k:nown. In that case it is usually necessary to solve a nonlinear differential equation of the Riccatti type. It is shown, however, that the stresses along the axis of symmetry can be determined relatively simply in the case of problems characterized by isometric principal stress trajectories. In order to find out whether the trajectories are isometric, we apply the test which has been proposed already by Neuber; it consists in equating the boundary stresses to a certain function inversely proportional to the quadratic form.The method of isochrome image analysis on illustrated by an example.